Fostering sustainability: green tourism policy in Padang city, Indonesia - Yenita, Yenita (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
West Sumatera possesses a lot of natural wealth in terms of tourism aspects. However, it has not been used optimally, highlighting the need for a comprehensive analysis of public policies in the tourism district to achieve a tourist-friendly green tourism that could be use in the next 10 to 20 years. This research’s purpose is to discover the policies in West Sumatra’s district using a qualitative approach and to be supported from utilizing purposive sampling techniques by doing in-depth interviews and analyzing the results in the format of an interactive model. The outcome proves that the current West Sumatra’s policies did not provide a particular regulation in terms of implementation green tourism. Therefore, it is crucial to adopt a comprehensive cross-sectoral policy approach that actively engages stakeholders and other relevant actors in the development of a green tourism destination in Padang City. This approach is expected to significantly enhance the green tourism potential in Padang City across various related sectors, leading to improved community welfare. Furthermore, the involvement of tourism-conscious communities and various tourism actors is also expected to contribute to establishing Padang City as a prominent green tourist destination in West Sumatra. This study will offer valuable insights for the West Sumatra regional government and contribute to boosting both local and global tourist visits.